Educational upgrading and returns to skills in Latin America: Evidence from a supply-demand framework - Galiani, Sebastian (2017)
This paper documents the evolution of wage differentials and the supply of workers by educational level for sixteen Latin American countries over the period 1991-2013. We find a pattern of rather constant rise in the relative supply of skilled and semi-skilled workers over the period. Whereas the returns to secondary education fell over time, in contrast, the returns to tertiary education display a remarkable changing pattern common to almost all economies: significant increase in the 1990s, strong fall in the 2000s and a deceleration of that fall in the 2010s. We conclude that supply-side factors seem to have limited explanatory power relative to demand-side factors in accounting for changes in the wage gap between workers with tertiary education and the rest.